An Efficient and Secure m-IPS Scheme of Mobile Devices for Human-Centric Computing - Young-Sik Jeong; Jae Dong Lee; Jeong-Bae Lee; Jai-Jin Jung; Jong Hyuk Park (Journal of Applied Mathematics)
Recent rapid developments in wireless and mobile IT technologies have led to their application in many real-life areas, such as disasters, home networks, mobile social networks, medical services, industry, schools, and the military. Business/work environments have become wire/wireless, integrated with wireless networks. Although the increase in the use of mobile devices that can use wireless networks increases work efficiency and provides greater convenience, wireless access to networks represents a security threat. Currently, wireless intrusion prevention systems (IPSs) are used to prevent wireless security threats. However, these are not an ideal security measure for businesses that utilize mobile devices because they do not take account of temporal-spatial and role information factors. Therefore, in this paper, an efficient and secure mobile-IPS (m-IPS) is proposed for businesses utilizing mobile devices in mobile environments for human-centric computing. The m-IPS system incorporates temporal-spatial awareness in human-centric computing with various mobile devices and checks users’ temporal spatial information, profiles, and role information to provide precise access control. And it also can extend application of m-IPS to the Internet of things (IoT), which is one of the important advanced technologies for supporting human-centric computing environment completely, for real ubiquitous field with mobile devices.